2013
DOI: 10.1016/j.chom.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immunity Interact to Quench Microbiome Flagellar Motility in the Gut

Abstract: SUMMARY Gut mucosal barrier breakdown and inflammation have been associated with high levels of flagellin, the principal bacterial flagellar protein. Although several gut commensals can produce flagella, flagellin levels are low in the healthy gut, suggesting the existence of control mechanisms. We find that mice lacking the flagellin receptor Toll-like receptor (TLR) 5 exhibit a profound loss of flagellin-specific immunoglobulins (Ig) despite higher total Ig levels in the gut. Ribotyping of IgA-coated cecal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
291
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(314 citation statements)
references
References 51 publications
14
291
1
3
Order By: Relevance
“…À / À mice than wild-type mice (Cullender et al, 2013), as Bacteroidales do not have flagellin (Lozupone et al, 2012). In Rag1 À / À mice, a decrease in the abundance of Verrucomicrobiales with age was also observed (Figure 2a) but it was not statistically significant (Supplementary Table S2).…”
Section: Immunity Alters Microbiota H Zhang Et Almentioning
confidence: 84%
See 1 more Smart Citation
“…À / À mice than wild-type mice (Cullender et al, 2013), as Bacteroidales do not have flagellin (Lozupone et al, 2012). In Rag1 À / À mice, a decrease in the abundance of Verrucomicrobiales with age was also observed (Figure 2a) but it was not statistically significant (Supplementary Table S2).…”
Section: Immunity Alters Microbiota H Zhang Et Almentioning
confidence: 84%
“…It is thus conceivable that deficiencies in the host adaptive immune system would result in an altered microbiota. Indeed, such deficiency can lead to a markedly elevated level of bacterial flagellin (Cullender et al, 2013), which is normally kept low presumably by host immunity. In addition, mice deficient in recombination-activating gene 2 (Rag2) or activation-induced cytidine deaminase had increased segmented filamentous bacteria in the small intestine (Suzuki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior, called taxis [Krell et al, 2011, Purcell, 1977, has long been a subject of scientific investigation, as it serves a variety of purposes: seeking out nutrients and avoiding toxic substances Armitage, 2004, Adler, 1969], identifying thermal [Paster and Ryu, 2007] and oxygen [Adler et al, 2012] gradients, as well as aiding pathogenic species in infecting their hosts [Rivera-Chávez et al, 2013, Cullender et al, 2013. The understanding of bacterial taxis is not only important when it comes to bacterial motility and accumulation; it also serves as a model for biological signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…TLR5 recognizes flagellin, the main structural protein of bacterial flagella. Since TIV did not stimulate directly TLR5 and since the human gut can harbor many flagellated bacteria [11], our findings suggested that commensals could help boost TIV immunogenicity. The hypothesis that flagellin from gut microbes may act as a natural adjuvant of TIV vaccine was then tested in mice.…”
mentioning
confidence: 96%